CGIAR Research Program on Forests, Trees and Agroforestry - Plan of Work and Budget 2021 - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
In 2020, FTA was the subject of an independent review conducted by the CGIAR Advisory Services Shared Secretariat on behalf of the CGIAR System. The purpose of the review was to assess the extent to which FTA is delivering quality of science and demonstrating effectiveness in relation to its theory of change (ToC). The scope of the review focused on FTA activities and results that were reported from 2017, when the program started its second phase, until end of 2019.